Reivindicações, manifestações e movimentos sociais por transporte coletivo em Cuiabá no período de 1985 a 2014 - Assad, Kader Carvalho (2015)
Anchored in the perspective of totality, according to which social movements are historical processes, which stem from the inherent contradictions of the capitalist mode of production, this thesis analyzes the social struggles for public transport in Cuiabá in the period 1985-2014, seeking to know the determinations where they are and articulate the different subjects involved, as well as their mobilization processes, claim, control strategies and also the relations and mediations that are established in this process. The methodology used is qualitative, using the bibliographic and documentary research, through consultation with the daily newspapers in Cuiabá. The adopted analysis categories are: urban issues and urban social movements. The systematization of the data reveals that the price of the fare, the lack of fleet maintenance, overcrowding and the disrespect of times are the main complaints and claims related to transportation. Among collective subjects involved in the fight are the residents' associations, the student movement, the advocacy organizations and the Fight Committee for Public Transportation (CLTP), which from 2005 articulates these movements and organizations, giving more strength and visibility to the struggles. It was possible to identify two periods in the movement's history. In the first, 1985-2002, we observe generally isolated manifestations of each of these organizations. The second, from 2003 to 2014 there is the unification of the struggles through CLTP with qualitative changes not only in their forms of organization and expression, but also in the claims presented.